2021
DOI: 10.1055/a-1613-5747
|View full text |Cite
|
Sign up to set email alerts
|

Auswirkungen der COVID-19-Pandemie auf die logopädische Therapie von Kindern mit einer Sprachentwicklungsstörung

Abstract: Zusammenfassung Hintergrund Im Dezember 2019 begann sich die COVID-19-Pandemie weltweit auszubreiten und sorgte für massive Einschränkungen im täglichen Leben. Viele Bildungseinrichtungen und logopädische Praxen wurden vorübergehend geschlossen (sog. Lockdown). Kinder mit einer Sprachentwicklungsstörung waren gezwungen, ihre Therapie zu pausieren. Ziel dieser Studie war es zu beschreiben, ob und wie die logopädische Therapie während des Lockdowns durchgeführt wurde und welche psychische Belastung für… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Despite the numerous studies conducted during the global COVID-19 pandemic focusing on strategies and alternative language intervention methods, such as telepractice speech therapy ( 21 23 ), little is known about the specific impact of pandemic-induced intervention interruption on children with language delays. Hackenberg et al reported a high psychosocial burden experienced by parents of children with speech and language disorders due to therapy pause during the Covid-19 pandemic; however, the effects on their children's speech and language abilities were not addressed ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the numerous studies conducted during the global COVID-19 pandemic focusing on strategies and alternative language intervention methods, such as telepractice speech therapy ( 21 23 ), little is known about the specific impact of pandemic-induced intervention interruption on children with language delays. Hackenberg et al reported a high psychosocial burden experienced by parents of children with speech and language disorders due to therapy pause during the Covid-19 pandemic; however, the effects on their children's speech and language abilities were not addressed ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hackenberg el. reported parents of children with speech and language disorders had more fears and worries about their children's development ( 24 ). In a clinical setting, our study can alleviate parents' psychosocial burden and increase parental compliance and confidence in resuming intervention post-interruption.…”
Section: Discussionmentioning
confidence: 99%